2022
DOI: 10.34117/bjdv8n4-036
|View full text |Cite
|
Sign up to set email alerts
|

Implicações das boas práticas agropecuárias (BPAS) na redução dos índices de contagem de células somáticas (CCS) e contagem padrão em placas (CPP) em pequenas propriedades leiteiras no Município de Canindé de São Francisco-SE / Implications of good agricultural practices (BPAS) in the reduction of somatic cell count (CCS) and standard plate count (CPP) indices in small dairy farms in the Municipality of Canindé de São Francisco-SE

Abstract: O presente estudo descrever um relato de dois casos sobre os impactos da adoção das Boas Práticas Agropecuárias (BPAs) em duas propriedades leiteiras, no município de Canindé de São Francisco, no Alto Sertão Sergipano. As duas propriedades descritas apresentaram médias geométricas acima do exigido pela legislação na Contagem de Células Somáticas (CCS) (500.000 CS/mL) e Contagem Padrão em Placas (CPP) (300.000 UFC/mL), por isso, foi realizada uma visita técnica em ambas para evitar a terceira média geométrica a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After analyzing the data, it was verified that 27.3% and 63.6% of the milk producers in the study would have the interruption in the of the milk produced for presenting three consecutive monthly geometric means above the acceptable limits by the current normative instruction for SCC and SPC, respectively (Table 4). In a more recent work by Pereira et al (2022) evaluating small dairy farms of bovine milk in the state of Sergipe, the authors verified that for the results of SPC, the samples showed counts within the values required by law, after adopting sanitary measures with the use of alkaline detergents, acids and sanitizers for cleaning milking equipment. As for SCC, only one of the properties did not reduce the values, due to the producer's difficulty in separating healthy cows from cows with mastitis at the time of milking.…”
Section: Resultsmentioning
confidence: 77%
“…After analyzing the data, it was verified that 27.3% and 63.6% of the milk producers in the study would have the interruption in the of the milk produced for presenting three consecutive monthly geometric means above the acceptable limits by the current normative instruction for SCC and SPC, respectively (Table 4). In a more recent work by Pereira et al (2022) evaluating small dairy farms of bovine milk in the state of Sergipe, the authors verified that for the results of SPC, the samples showed counts within the values required by law, after adopting sanitary measures with the use of alkaline detergents, acids and sanitizers for cleaning milking equipment. As for SCC, only one of the properties did not reduce the values, due to the producer's difficulty in separating healthy cows from cows with mastitis at the time of milking.…”
Section: Resultsmentioning
confidence: 77%